Exploring the influence of an extended theory of planned behaviour on preferences and willingness to pay for participatory natural resources management. (15th February 2019) - Grilli, Gianluca; Notaro, Sandra
Abstract: In this paper we explore the role of the theory of planned behaviour in the context of preferences for a decentralized governance of natural resources. A choice experiment was carried out to elicit preferences of the tourists for alternative options of natural resource management in a case study in Italy and data were collected by means of personal interviews. Indicators to assess the planned behaviour of respondents were collected by means of Likert scales that were then included in the choice model. Differently from previous research on planned behaviour we use an extended version of the theory that includes moral norms and explicitly account for endogeneity of the indicators with a hybrid mixed logit model, in which a latent variable is used to explain both answers to the indicators and management choices. Results suggest a general preference of respondents for local governance and indicate that the latent variable has a significant effect on explaining preference heterogeneity and improve model fit. In addition, results suggest that the theory of planned behaviour is appropriate to model individuals' behavioural intention and can be used to tailor marketing activities aiming at increasing people's pro-environmental behaviours. Highlights: We tested the effect of the theory of planned behaviour on preferences for local governance. We used a hybrid mixed logit model to analyse the data. We found a significant effect of TPB indicators on preferences. The hybrid model performed better than the baseline. Results suggested that TPB explains preference heterogeneity and should be considered for an effective destination management.